Beijing is haunted by Olympic ghosts - Gudrun Wacker (Stiftung Wissenschaft und Politik (SWP), 2008)
The controversy over the upcoming Olympic Games in Beijing has increased markedly due to the violent demonstrations and events in Tibet: While in the West protests and calls for a boycott have grown louder, a nationalist reaction has been forming in China. A black and white perspective dominates media reporting on both sides. A few months before the Olympics, China and the West are caught in dilemmas and it will be hard to find a constructive way out. Efforts should be made nevertheless, since the current polarisation of opinions helps nobody - and least of all human rights in China
Keywords: 320